COMPUTATIONAL MODELING THE SUPERHEATED STEAM FLOWS INTO THE SETTING PARTS OF MICROTURBINE AND EFFICIENCY ESTIMATION FOR IMPROVEMENT OF TURBOAGGREGATE CONSTRUCTION - A. M. Krot; P. P. Tkachova; I. N. Spagar (Informatika)
The main stages of mesh creation and computational modeling the superheated steam flows into the setting parts of microturbine based on modern program packages have been considered. A method for energy loss calculation into the setting parts of microturbine and efficiency estimation based on computational modeling the superheated steam flows (arising from fluid converter rotation) has been developed. To improve turbo-aggregate construction the finite element model of the setting parts of microturbine has been modified. Further computational modeling the superheated steam flows into the modified setting parts of micro-turbine showed the efficiency increasing on 3 %.